Mesocrystalline Ordering and Phase Transformation of Iron Oxide Biominerals in the Ultrahard Teeth of Cryptochiton stelleri. Issue 4 (9th February 2022) - Wang, Taifeng; Huang, Wei; Pham, Cong Huy; Murata, Satoshi; Herrera, Steven; Kirchhofer, Nathan D.; Arkook, Bassim; Stekovic, Dejan; Itkis, Mikhail E.; Goldman, Nir; Zepeda-Ruiz, Luis; Freychet, Guillaume; et al.
Abstract : Biological organisms naturally synthesize complex, hierarchical, multifunctional materials through mineralization processes at ambient conditions and under physiological pH. One such example is the ultrahard and wear‐resistant radular teeth found in mollusks, which are used to scape against the rock to feed on algae. Herein, the biologically controlled structural development of the hard, outer magnetite‐containing shell of the chitin teeth is revealed. Specifically, the formation of a series of mesocrystalline iron oxide phases, templated by chitin‐binding proteins, is identified. The initial domains, consisting of ferrihydrite mesocrystals with a spherulite‐like morphology, undergo a solid‐state phase transformation to form magnetite while maintaining mesocrystallinity, likely via a shear‐induced solid‐state reaction, without any noticeable architectural changes. Subsequent growth via Ostwald ripening leads to nearly single‐crystalline rod‐like elements. In addition, an interpenetrating organic matrix is identified that, at early stages of tooth development, potentially contains iron‐binding proteins that guide the self‐assembly of the mesocrystalline mineral and influence the preferred orientation of the later‐formed magnetite nanorods, which ultimately determines the mechanical behavior of the mature chiton teeth. Abstract : Chiton has ultrahard teeth to scape on the rock for food. In the maturation process of chiton's teeth, an organic‐controlled mesocrystalline iron oxide spherulite system is revealed, and the detailed phase transformation with structural development is thoroughly determined. The understanding of biomineralization shed a light on the eco‐friendly synthesis of wear‐resistant engineering materials.